2014
DOI: 10.1111/lam.12319
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of Zataria multiflora Boiss. essential oil effect on biogenic amines formation and microbiological profile in Gouda cheese

Abstract: The presence of biogenic amines in cheese has a serious impact on public health. Besides, there is growing concern about the use of chemical preservatives and the food industry is looking for new natural preservation methods. Zataria multiflora Boiss. essential oil is well known for its antimicrobial effects, and we attempted to reduce biogenic amines formation in Gouda cheese using Z. multiflora Boiss. essential oil as a natural additive. Furthermore, the desirable organoleptic qualities such as flavour, odou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
(113 reference statements)
1
5
0
Order By: Relevance
“…Similar outcomes have been shown by Josipović et al (2015) and Tornambé et al (2008) 24,39 . Also, Es’Haghi Gorji et al (2014) reported that cheese incorporated with 0.2% EOs had the highest score in organoleptic properties 40 …”
Section: Resultssupporting
confidence: 74%
“…Similar outcomes have been shown by Josipović et al (2015) and Tornambé et al (2008) 24,39 . Also, Es’Haghi Gorji et al (2014) reported that cheese incorporated with 0.2% EOs had the highest score in organoleptic properties 40 …”
Section: Resultssupporting
confidence: 74%
“…The amount of microorganisms in cheeses depends on many factors, among others fresh milk quality, technological processes applied (pasteurization, starter cultures addition, time and temperature of thermo-mechanical curd treatment, salting), time and temperature of ripening, and many others (Beresford and Williams 2004; Es’haghi Gorji et al 2014; Fuentes et al 2015; Flasarová et al 2016). Fuentes et al (2015) and Beresford and Williams (2004) observed that the count of microorganisms in ripened cheeses was at about 8 log cfu g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of BAs in cheese and other foods is a matter of public health concern (11). Cheeses, especially those made with raw milk, are complex ecosystems populated by microbes with diverse metabolic abilities (55).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, BAs were proposed to be food safety indicators and biomarkers for several diseases (9,10). Among fermented foods, cheeses containing high concentration of BAs may have a serious impact on public health (11). After fish, cheese is the second most frequently reported foodstuff responsible for hista-mine intoxication (12,13).…”
mentioning
confidence: 99%